2019
DOI: 10.3389/fpsyg.2019.00673
|View full text |Cite
|
Sign up to set email alerts
|

Humble Leadership and Employee Resilience: Exploring the Mediating Mechanism of Work-Related Promotion Focus and Perceived Insider Identity

Abstract: Although the topic of employee resilience has recently received increased attention, existing research has largely failed to explore its situational triggers. Drawing on social information processing theory, the current study integrates the literature of humility and resilience to theorize the underlying mechanism through which humble leadership facilitates employee resilience. This research proposes a potential heterogeneous effect that humble leadership catalyzes employee resilience through multiple pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 63 publications
(118 reference statements)
7
97
0
4
Order By: Relevance
“…The results of structural equation simulation show that the direct effect of HP on entrepreneurial persistence and enterprise performance is not significant, while the direct effect of compulsive passion on entrepreneurial persistence and enterprise performance is significant. Harmonious passion and compulsive passion are significantly correlated with entrepreneurial self-efficacy, and self-efficacy plays an intermediary role between entrepreneurial passion and entrepreneurs' psychology and behavior (Zhu et al, 2019). The hypothesis proposed is basically valid.…”
Section: Resultsmentioning
confidence: 82%
“…The results of structural equation simulation show that the direct effect of HP on entrepreneurial persistence and enterprise performance is not significant, while the direct effect of compulsive passion on entrepreneurial persistence and enterprise performance is significant. Harmonious passion and compulsive passion are significantly correlated with entrepreneurial self-efficacy, and self-efficacy plays an intermediary role between entrepreneurial passion and entrepreneurs' psychology and behavior (Zhu et al, 2019). The hypothesis proposed is basically valid.…”
Section: Resultsmentioning
confidence: 82%
“…However, if the creative thinking of employee conflicts with the development goals of the company, they will be considered as performing deviant innovation behaviors. This study explores the psychological capital of entrepreneurship and deviant innovation behavior of employees separately (Zhu et al, 2019). After analyzing the research results, the authors found that there is a significant correlation among entrepreneurial psychological capital, entrepreneurial opportunity ability, and entrepreneurial performance; there is a significant correlation between entrepreneurial psychological capital and entrepreneurial opportunity ability; there are respective significant correlations between the work values and psychological empowerment of employees, between the work values and deviant innovation behaviors of employees, and between the psychological empowerment and deviant innovation behaviors of employees (Zheng and Liu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After the investment is over, both parties should carry out thorough interests and division of power to ensure the interests of both parties. Also, the two parties can sign some substantial reward regulations, such as the investor's income directly determines the investing institution's income, and the investor introduces the corresponding client to the investing institution (Rogoza et al, 2018;Zhu et al, 2019).…”
Section: Solutions For Information Asymmetrymentioning
confidence: 99%